Wiki: University Teaching: roles and challenges - Araújo, Francys Silva (2012)
This text brings the experience of a collaborative textual construction (wiki) in a virtual learning environment in which 36 professors from different areas of knowledge at UFMG discuss the roles and challenges of teaching in higher education. This activity is offered in the III Formative Pathways of Teaching in Higher Education, in line with the proposal of promoting reflection and improvement of teaching practices at UFMG. This formation was sponsored by GIZ - Development Practices in Higher Education Network, board linked to the Rectory of Graduation.